Persist - Elizabeth Warren (New York Metropolitan Books, 2021)
Elizabeth Warren is a beacon for everyone who believes that real change can improve the lives of all Americans. Committed, fearless, and famously persistent, she brings her best game to every battle she wages.
Includes bibliographical references (pages 245-284) and index.
Keywords: Women presidential candidates--United States--Biography.